Developing a predictive understanding of landscape importance to the Punan-Pelancau of East Kalimantan, Borneo - Cunliffe, R.N.; Lynam, T.J.P.; Sheil, Douglas; Wan, M.; Salim, A.; Basuki, I.; Priyadi, H. (2006)
In order for local community views to be incorporated into new development initiatives, their perceptions need to be clearly understood and documented in a format that is readily accessible to planners and developers. The current study sought to develop a predictive understanding of how the Punan Pelancau community, living in a forested landscape in East Kalimantan, assigns importance to its surrounding landscapes and to present these perceptions in the form of maps. The approach entailed the iterative use of a combination of participatory community evaluation methods and more formal modeling and geographic information system techniques. Results suggest that landscape importance is largely dictated by potential benefits, such as inputs to production, health, and houses. Neither land types nor distance were good predictors of landscape importance. The gridcell method, developed as part of the study, appears to offer a simple technique to capture and present the knowledge of local communities, even where their relationship to the land is highly complex, as was the case for this particular community.